Using Web and Paper Questionnaires for Data-Based Decision Making From Design to Interpretation of the Results. - Thomas, Susan J. (1-Off., 2004)
Offering suggestions for successfully using both Web-based and paper-based questionnaires, this practical handbook provides authoritative guidance for planning a survey project, and communicating the results to a variety of audiences.